PENGARUH CORPORATE SOSIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2009-2011) - Novrianti, Vesy; Armas, Riadi (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2012)
The background of this research is the condition of company that decreases because of theeconomy crisis in Asia by the year 1997 particularly for the registered manufacturecompanyin Indonesia Stock Exchange. It needs to apply Corporate Sosial Responsibility and GoodCorporate Governance in increasing the performance of company. Based on the backgroundabove, this research aims to know whether or not there is influence of the Corporate SosialResponsibility and Corporate Governance that consist of Managerial Ownership,Institutional Ownership, Size board of Director, Commissioner Independent and Size of theAudit Committee simultaneously and partially to the companies manufactures’ performancein Indonesia Stock Exchange. The total number ofsample in this research is 11 manufacturecompanies from 2009 to 2011. The data used is secondary data in the form of report retrievedin www.idx.co.id and Capital Market Information Center (PIPM). Independent variableused by researcher is Corporate Sosial Responsibility and Good Corporate Governance. Theresearcher also used multiple regression linear technique analysis. The research findingsshow that: (1) CSR and GCG give the influence simultaneously to the company’sperformance; (2) CSR does not give influence partially to the company’s performance (ROE)and GCG: Managerial Ownership, Institutional Ownership, Size board of Director, and Sizeof the Audit Committee does not give influence to the company’s performance (ROE) andonly Commissioner Independent give influence partially to the company’s performance(ROE).Key words: Corporate sosial responsibility and good corporate governance and company’sperformance